2010
DOI: 10.1103/physrevb.81.020511
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting state with a finite-momentum pairing mechanism in zero external magnetic field

Abstract: In the BCS theory of superconductivity, one assumes that all Cooper pairs have the same center of mass momentum. This is indeed enforced by self consistency, if the pairing interaction is momentum independent. Here, we show that for an attractive nearest neighbor interaction, this is different. In this case, stable solutions with pairs with momenta q and −q coexist and, for a sufficiently strong interaction, one of these states becomes the groundstate of the superconductor. This finitemomentum pairing state is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 16 publications
6
81
1
Order By: Relevance
“…A BCS-mean-field-theory of a extended Hubbard model in two dimensions has been developed by Loder and coworkers 21,22 who found that, as part of a rich phase diagram, the PDW is the ground state for large enough interactions. Earlier mean field theory results in the t−J model by Yang et al 23 found that the PDW is energetically very close to being the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…A BCS-mean-field-theory of a extended Hubbard model in two dimensions has been developed by Loder and coworkers 21,22 who found that, as part of a rich phase diagram, the PDW is the ground state for large enough interactions. Earlier mean field theory results in the t−J model by Yang et al 23 found that the PDW is energetically very close to being the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a microscopic model, it was shown in reference [33] that a PDW state cannot result from an on-site pairing interaction. However, the PDW state can be a stable alternative for unconventional superconductors with gap nodes, specifically for d-wave superconductivity as realized in the high-T c cuprate superconductors.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless it is still assumed that pairing occurs only for one specific angular momentum q. For conventional superconductors, this assumption is generally true, although for superconductors with gap nodes, the situation may be different, as was shown for d-wave pairing symmetry in reference [33]. In this section, we use the 1 In the literature the symmetric…”
Section: Superconducting State: Emergence Of a New Periodicitymentioning
confidence: 99%
“…16 In a series of papers, Loder and collaborators 17,18 found that a PDW superconducting state is preferred in a tight-binding model with strong attractive interactions (although the critical value of the coupling constant above which the PDW is stable is presumably outside the range of validity of the weak coupling theory). Similarly, PDW states with broken time-reversal invariance and parity have been found recently 19,20 in a 'hot spot' model, which also requires a critical (and typically not small) value of a coupling constant.…”
Section: -11mentioning
confidence: 99%
“…(4.2)) has pockets of Bogoliubov quasiparticles, as it is also found in the weak coupling theories. 4,14,17,44,50,51 The size of the pockets depends on the strength of the SC gap. In addition, we compute the spectral function given by (see for instance Ref.…”
mentioning
confidence: 99%